Probing Neural Transplant Networks In Vivo with Optogenetics and Optogenetic fMRI - Andrew J. Weitz; Jin Hyung Lee (Stem Cells International)
Understanding how stem cell-derived neurons functionally integrate into the brain upon transplantation has been a long sought-after goal of regenerative medicine. However, methodological limitations have stood as a barrier, preventing key insight into this fundamental problem. A recently developed technology, termed optogenetic functional magnetic resonance imaging (ofMRI), offers a possible solution. By combining targeted activation of transplanted neurons with large-scale, noninvasive measurements of brain activity, ofMRI can directly visualize the effect of engrafted neurons firing on downstream regions. Importantly, this tool can be used to identify not only whether transplanted neurons have functionally integrated into the brain, but also which regions they influence and how. Furthermore, the precise control afforded over activation enables the input-output properties of engrafted neurons to be systematically studied. This review summarizes the efforts in stem cell biology and neuroimaging that made this development possible and outlines its potential applications for improving and optimizing stem cell-based therapies in the future.